A Study of the Bonding Properties Between Rubber Concrete and Reinforcing Steel (Comprehensive Journal of Science, 2026)
Proper bonding between concrete and rebar is crucial, and due to the problems caused by rubber tire waste and the significant environmental problems it causes, in recent years, many studies have been conducted on the addition of recycled rubber from tires in concrete mixtures and its effect on the bonding properties between concrete and rebar.    This research deals with the study of the bond between rubber concrete and rebar, with the aim of evaluating the effect of the use of rubber and treated rubber on the performance of concrete. The study includes the preparation of a reference mixture, a mixture containing 30% rubber as a partial substitute for fine aggregates, in addition to a mixture containing 30% rubber treated with cement mortar as a partial substitute for fine aggregates. The ratio of water to cement was constant in all mixtures (w/c = 0.4).Different diameters of rebar (10, 12, 14) mm were used to study the effect of rebar diameter on bonding with rubber concrete. Mechanical tests were conducted for the concrete, including compressive strength testing, indirect tensile strength testing and drag testing.    The results of this research showed that adding rubber to concrete leads to a reduction in the compressive resistance and bonding strength of concrete with rebar. The results also showed that the treatment of rubber with cement mortar showed a slight improvement in these properties compared to untreated rubber. The reference mixture was the best in terms of performance and it was concluded that the lower the diameter of the rebar, the greater the cohesion stress between it and the rubber concrete.
Keywords: Rubberized concrete Recycled tires Reinforcing steel (Rebar) Bond strength between concrete and reinforcement Compressive strength Indirect tensile strength Pull-out test Fine aggregate replacement Cement mortar treatment of rubber Sustainable concrete